Circular Economy for the Raja Ampat Ecotourism Development: Perils, Potentials, and Study Cases Discourse - Jhuswanto, Farhan Riswandha; Nurul Fajriyah (Journal of World Trade Studies, 2023)
This article aims to analyze the development of ecotourism in Raja Ampat through the circular economy concept. A qualitative method is used in this study by compiling findings from various studies on ecotourism worldwide, especially in the local practice. Raja Ampat has become one of Indonesia's most popular tourist destinations, enhanced with extraordinary natural resources and its tourism attractiveness, which gives it potential in improving its ecotourism. However, perils like government support, insufficient technology, and community readiness were taken into account. Despite that, efforts were made to develop ecotourism in Raja Ampat through the development of eco-friendly infrastructures, workshops regarding the management of sustainable tourism, and involving locals in educational campaigns related to preserving natures in Raja Ampat. As a result, these efforts are considered for a significant increase in some infrastructural developments. These efforts indirectly had a positive impact on the economy of the locals. The Raja Ampat ecotourism development is in line with the circular economy, especially on the focus of tourist management that reinforces local and natural resources in a sustainable manner.